2002
DOI: 10.1038/sj.bjp.0704914
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of neurotensin in NANC relaxation of longitudinal muscle of the jejunum and ileum of Wistar rats

Abstract: 1 The mediators of nonadrenergic, noncholinergic (NANC) relaxation in longitudinal muscle of the jejunum and ileum of Wistar rats were examined in vitro. 2 Treatment of the jejunal and ileal segments with a-chymotrypsin resulted in decreases in the NANC relaxations induced by electrical ®eld stimulation (EFS) by about one half. 3 The NANC relaxations were also decreased by about one half after the segments had been desensitized to neurotensin. A neurotensin receptor antagonist, SR48692 (10 mM) inhibited the NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…In the presence of atropine (1 mM) and guanethidine (5 m M), EFS with two pulses of 20-Hz frequency at 20 V induced mono-phasic rapid i.j.ps. The i.j.ps were completely inhibited by apamin as shown previously (23). SR48692 at 10 m M also partially inhibited the i.j.ps and resulted in about 30% inhibition 20 min after treatment, i.j.ps in the absence or presence of SR48692 were 12.6 ± 1.6 mV (n = 8) or 8.8 ± 2.0 mV (n = 8, significantly different from the value in the absence, P<0.05), respectively (Fig.…”
Section: Effects Of A3p5ps On the Efs-induced Ijps And Effects Of Asupporting
confidence: 84%
See 4 more Smart Citations
“…In the presence of atropine (1 mM) and guanethidine (5 m M), EFS with two pulses of 20-Hz frequency at 20 V induced mono-phasic rapid i.j.ps. The i.j.ps were completely inhibited by apamin as shown previously (23). SR48692 at 10 m M also partially inhibited the i.j.ps and resulted in about 30% inhibition 20 min after treatment, i.j.ps in the absence or presence of SR48692 were 12.6 ± 1.6 mV (n = 8) or 8.8 ± 2.0 mV (n = 8, significantly different from the value in the absence, P<0.05), respectively (Fig.…”
Section: Effects Of A3p5ps On the Efs-induced Ijps And Effects Of Asupporting
confidence: 84%
“…It was previously shown that apamin significantly inhibited EFS (10 Hz)-induced relaxation of the jejunal segments by 83% (23). Apamin at 100 nM completely inhibited the relaxation at 1.0 Hz (Table 1).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations